Financial development and growth: Evidence from Bayesian Modelling - Ferdinand Ahiakpor; Ralph Essem Nordjo; Samuel Erasmus Alnaa (Cogent Economics & Finance, 2023)
This paper examines the nexus between financial development and economic growth in Ghana between 1970 and 2020. The study adopted the Bayesian Model Averaging (BMA) techniques to address issues of model uncertainty due to many potential explanatory variables that could influence growth. The study revealed that credit to the private sector, gross domestic savings, inflation rate, labour force participation, current account balance and population growth as key promoters of growth. Therefore, there is the need to address cost of doing business and promote increased credit delivery to the private sector. The direct association between financial development and growth indicates the need for policy makers to implement measures such as provision of legal environment for efficient allocation of credit to the private sector and provide the environment for the establishment of more financial institutions to enhance the growth of the financial sector.
Keywords: C3; G2; G28; 330; BMA; Economic Growth; Financial Development and Ghana